Kajian Potensi dan Prioritas Lokasi Dry Port di Malang dan Pasuruan - Rahadi Bintang; Harnen Sulistyo; Muhammad Zainul Arifin (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2016)
The objectives of this study are knowing the current logistic performance based on customers perceptions, knowing the probability of dry port’s usage and the recommendations of dry port location with high priority in Malang and Pasuruan. This study uses Principle component analysis, stated preference dan analytic hierarchy process. Based on the results, the logistic performance index of Tanjung Perak Port-Malang route is 3.4, relatively even with Tanjung Perak Port-Pasuruan route that has index 3.41 at likert scale. For the both routes, commodity and transportation infrastructure have low score, less than 3 at likert scale. The probability usage is 88.95% when dry port gives3 days shorter in dwelling time, predicted lead time, five hundred thousand rupiahs cheaper in transportation and storage cost and 2 hours faster in travel time for logistic activities of a 20 feet container on Tanjung Perak Port-Pasuruan route. Pasuruan with priority weight 57.66% is more prioritized than Malang which has priority weight 42.34% as dry port location.To optimize the implementation of dry port in proposed location, increasing the commodity, transportation infrastructure and cargo clearance services at dry port integrated to seaport are recommended